Franco’s and Giardinelli’s women: stereotypical representations of femininity in Rosario Tijeras, Paraíso Travel, Luna caliente and El décimo infierno novels (Islas, 2019)
Literature can legitimate or rebuild new social imaginaries. From this perspective, this research paper proposes as research question: which are the characteristics of the feminine gender constructions recurrent in the novels Rosario Tijeras and Paraíso Travel, by Jorge Franco and Luna Caliente and El décimo infierno, by Mempo Giardinelli? This paper´s general research objective is to identify the construction characteristics of the feminine gender in the novels above mentioned with communicologic categories.
Keywords: gender; gender theories; gender and literature; feminism and gynocritics; comunication